2008
DOI: 10.1002/ange.200704199
|View full text |Cite
|
Sign up to set email alerts
|

Template‐Assembled Synthetic G‐Quartets (TASQs)

Abstract: Ein ungewöhnliches Quartett: Das Anheften von vier Guaninresten an einen Cavitanden lieferte eine Verbindung, die in CDCl3 templatvermittelt eine lipophile synthetische G‐Quartett(TASQ)‐Struktur ergab. Die Struktur ist im kationenfreien Zustand ungewöhnlich stabil. Dieser kationenfreie Korb sowie mögliche analoge kationengebundene Quartette und kationeninduzierte Quadruplexe könnten therapeutisch nützlich sein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…higher-order structures made of successive quadruplex units that result from the folding of long G-rich telomeric fragments) (24). In the course of our study, we found a way to improve the DNAzyme activities of both monomeric and multimeric quadruplexes by the use of a synthetic G-quartet (known as TASQ, for Template-Assembled Synthetic G-Quartet) (25,26), namely DOTASQ [for DOTA-templated Synthetic G-Quartet (27)]: the concomitant use of DNA and DOTASQ enables the hemin to be sandwiched at both extremities of quadruplex architectures, thereby being in a pocket whose hydrophobicity is optimal for catalyzing efficiently the peroxidatic process. The boosting effect of DOTASQ was efficient but modest (up to 6-fold) and enabled to lower the limit for reliable DNA detection at ∼500 nM scale.…”
Section: Introductionmentioning
confidence: 99%
“…higher-order structures made of successive quadruplex units that result from the folding of long G-rich telomeric fragments) (24). In the course of our study, we found a way to improve the DNAzyme activities of both monomeric and multimeric quadruplexes by the use of a synthetic G-quartet (known as TASQ, for Template-Assembled Synthetic G-Quartet) (25,26), namely DOTASQ [for DOTA-templated Synthetic G-Quartet (27)]: the concomitant use of DNA and DOTASQ enables the hemin to be sandwiched at both extremities of quadruplex architectures, thereby being in a pocket whose hydrophobicity is optimal for catalyzing efficiently the peroxidatic process. The boosting effect of DOTASQ was efficient but modest (up to 6-fold) and enabled to lower the limit for reliable DNA detection at ∼500 nM scale.…”
Section: Introductionmentioning
confidence: 99%
“…Keywords: DNA recognition · Gquadruplexes · heterocycles · ligand design · polycycles currently the focus of intense attention with the aim to decipher their biological roles [6] and to evaluate their potential for building DNA-based nanoobjects. [7] Interestingly, quadruplexes may bind small molecules, which in turn stabilize these structures and may act as molecular silencers by shifting a functional DNA conformation (duplex) to a nonfunctional one (quadruplex). Over the past decade, the search for small molecules acting as quadruplex ligands has developed dramatically with essentially two major goals: finding probes to sense quadruplex formation in various biological contexts and discovering new DNA-interacting agents of potential therapeutic interest.…”
Section: Introductionmentioning
confidence: 99%
“…Despite a large number of examples that use this template, to our knowledge, it has not been applied for the design of a specific folded structure of nucleic acid. [11] With this in mind, we investigated the use of a peptidic scaffold as a topological template that directs the intramolecular assembly of covalently attached oligonucleotides into a single characteristic folding topology of G quadruplex. We anticipated that the scaffold should permit the preorganization of the DNA strands and the stabilization of the quadruplex structure.…”
mentioning
confidence: 99%